Composição da dieta da espécie vulnerável Megalops Atlanticus (Elopiformes, Megalopidae) em estuário altamente urbanizado da região semiárida do Brasil - Matias, Grazielly Bandeira (2024)
Estuaries are nurseries for various fish species, providing shelter and nourishment during their early life stages. Embedded in complex trophic networks, these fish transfer energy between trophic levels and ecosystems but are affected by environmental changes and anthropogenic pressures, such as pollution and urbanization. The fish Megalops atlanticus, classified as vulnerable by the International Union for Conservation of Nature (IUCN), occurs in urbanized estuaries like the Rio Cocó, where the largest population of the species in the region has been observed. The aim of this study is to evaluate the diet of juvenile specimens in the Rio Cocó estuary through the taxonomic and molecular identification of items found in the stomach contents. The genetic material of the fish found in the stomach was amplified, purified, and sequenced for taxonomic confirmation using the 16S ribosomal marker and an online database. Specimens of this species, collected between 2017 and 2023 in the Rio Cocó (CE), indicate that juveniles of M. atlanticus feed on native and non-native invertebrates and fish in anthropized environments. The Rio Cocó estuary favors the occurrence of juveniles of M. atlanticus due to the availability of food and the adaptive behaviors of this species, such as migration to freshwater. However, this ecosystem is highly urbanized and subject to the discharge of anthropogenic effluents. The diet of M. atlanticus varies with growth, shifting from invertebrates to fish, and the population has a flexible feeding strategy, consuming native and non-native species like Oreochromis niloticus. The high pollution indicator invertebrate Tubifex sp. was the most consumed item by M. atlanticus in the Rio Cocó between 2022 and 2023. This study confirmed the generalist diet of M. atlanticus in the Rio Cocó estuary and indicated that this environment offers favorable biotic and abiotic conditions for the establishment of juveniles. Conservation strategies should focus on restructuring food webs, considering native species, and on habitat connectivity. Indeed, preserving the natural conditions of the Parque Estadual do Cocó estuary is crucial for the occurrence of these juveniles in this environment. Prohibiting the fishing of juvenile M. atlanticus and disseminating information about biology and dynamics of fishing this species are important measures for conservation.